2011
DOI: 10.1515/ijdhd.2011.043
|View full text |Cite
|
Sign up to set email alerts
|

Expecting my child to become “dragon” – development of the Chinese Parental Expectation on Child’s Future Scale

Abstract: This paper describes a study in which an assessment tool of parental expectation on child ' s future was developed. Based on focus group interviews of parents and adolescents in Hong Kong, fi ve dimensions of parental expectation on child ' s future were identifi ed, including " educational achievement " , " self-reliance " , " occupation " , " family obligation " , and " conduct " . In conjunction with the Chinese literature on parental expectations, the Chinese Parental Expectation on Child ' s Future Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Based on the literature of parental expectations (Brody, Flor, & Gibson, 1999;Davis-Kean, 2005) and parents' attributes of an ideal child (Shek & Chan, 1999), an indigenous scale assessing parental expectations on children's future was developed in five dimensions: educational achievement, self-reliance, occupation, family obligation, and conduct (J. T. Y Leung & Shek, 2011a). A 17-item measure was assessed in a previous validation study that showed internal consistency, divergent validity, and factorial validity (J. T. Y Leung & Shek, 2011c).…”
Section: Parental Expectations Of Children's Future Scale (Pecf)mentioning
confidence: 99%
“…Based on the literature of parental expectations (Brody, Flor, & Gibson, 1999;Davis-Kean, 2005) and parents' attributes of an ideal child (Shek & Chan, 1999), an indigenous scale assessing parental expectations on children's future was developed in five dimensions: educational achievement, self-reliance, occupation, family obligation, and conduct (J. T. Y Leung & Shek, 2011a). A 17-item measure was assessed in a previous validation study that showed internal consistency, divergent validity, and factorial validity (J. T. Y Leung & Shek, 2011c).…”
Section: Parental Expectations Of Children's Future Scale (Pecf)mentioning
confidence: 99%
“…Though the concept of parental expectation on child ' s future is distinctive and important in understanding family beliefs and processes in the Chinese context, research on the relevant area is minimal (5) . The paucity of research on parental expectations on child ' s future may be due to the diffi culties on theorization and conceptualization of beliefs, the culturalspecifi city of belief system, as well as the lack of measurement tools in measuring parental beliefs and expectations (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two focus groups of parents and adolescents were arranged and interviewed separately to understand their perceptions and experiences on parental expectations on child ' s future. Five dimensions of parental expectations on child ' s future emerged in the qualitative data, including " educational achievement " , " self-reliance " , " occupation " , " family obligation " , and " conduct " (5) . The dimensions refl ect the central features of Confucian thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature of parental expectations of children ' s future [43 -45] and parents ' attributes of an ideal child [46] , as well as qualitative fi ndings from focus groups of parents and adolescents, an indigenous scale assessing the parental expectation of children ' s future was developed [4] . The scale was developed with 23 items measuring the dimensions of parental expectations on the children ' s future in terms of educational achievement, self-reliance, occupation, family obligation, and conduct.…”
Section: Parental Expectations Of Children ' S Future Scale (Pecf)mentioning
confidence: 99%
“…Similarly, a computer search using the search terms " poverty/economic disadvantage " and " parental belief " of Social Work Abstracts in November 2011 for the period 1980 -2011 showed only one publication. The minimal research on parental beliefs of poor families may be due to the difficulties in the theorization and conceptualization of belief systems, cultural specificity of belief systems, and the lack of tools for measuring parental beliefs [4] . Sigel and McGillicuddy-De Lisi ( [5] , p. 497) stated that " a clear conception of beliefs [for parents] and theoretical explanations of how and why beliefs are effective are lacking " and that literature on beliefs " is superficial, poorly defined, and while often in face validity, it is sorely lacking in providing information about construct and content validity " .…”
Section: Introductionmentioning
confidence: 99%